Peri-implant health after microvascular head and neck reconstruction: a retrospective analysis : original article - Hoffmann, Korbinian; Büsch, Christopher; Moratin, Julius; Ristow, Oliver; Hoffmann, Jürgen; Mertens, Christian (Clinical oral implants research, 2023)
Introduction Prosthodontic rehabilitation after reconstruction with microvascular revascularized free flaps following ablative tumor surgery is challenging due to the altered anatomical and functional conditions. The aim of this retrospective study was to determine whether the type of graft and the type of peri-implant tissue have an effect on peri-implant inflammatory parameters and implant survival. Materials and Methods Patients who received a free flap reconstruction with subsequent implant-prosthetic rehabilitation between 2010 and 2022 were retrospectively included. The primary outcome variable was the probing depth (PPD) at a minimum of 1 year after completion of prosthetic restoration. Predictive variables were type of free flap, emergence profile, and history of radiation. Results Seventy-one patients after free flap reconstruction were included in the analysis. At a minimum of 24 months after implant insertion the primary outcome, PPD showed no clinically relevant differences between the types of free flaps used. The emergence profile through a skin island resulted in an increase in BOP compared to native mucosa in the descriptive analysis (p-value > .05). The analysis showed a 5-year implant survival of 96.2% (95% CI: 0.929-0.996) in cases without irradiation and 87.6% (95% CI: 0.810-0.948) with irradiation of the region evaluated (p-value .034). Conclusion Flap and associated soft tissue type had no significant effect on 5-year implant survival or peri-implant inflammatory parameters. However, the large heterogeneity of the patient population indicates that further prolonged studies are required for a more differentiated assessment of the long-term success.
Gesehen am 18.01.2024